(untitled) (Revista Internacional de Folkcomunicação, 2020)
In this article, we discuss how the craft cultural practices of Mariana (MG) are constituted in dialogue with mediatization. We reflect on how the mixtures with the media affect the cultural practices with the contributions of Canclini (2010,2015) and Certeau (2009). Methodologically, we have taken photos of craft productions exhibited in 13 craft stores in Mariana (MG) and interviewed 18 artisans from the city between 2016 and 2018. The interpretative analysis of this material was carried out. From this, we realize that the cultural craft cultural practices are affected by the media, so that they show a tension and a reconfiguration of their traditional forms and their creative possibilities in the current context. Craft cultural practices; Mediatization; Interactional processes; Consumption.